Biodiversita delle Aleocharinae della Cina: Il Genere Oxypoda (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2012)
Description of 47 new species of the genus Oxypoda: O. yunnanicola n. sp., O. mediogranulosa n. sp., O. irrepta n. sp., O. sinopusilla n. sp., O. meandrifera n. sp., O. guanxianensis n. sp., O. mimobisinuata n. sp., O. implorans n. sp., O. hastata n. sp., O. hailuogouensis n. sp., O. tibetana n. sp., O. sinofortis n. sp., O. qionglaimontis n. sp., O. daxuemontis n. sp., O. dilatatiapex n. sp., O. tridentis n. sp., O. jiudingensis n. sp., O. cavazzutii n. sp., O. zhagaensis n. sp., O. sinoperexilis n. sp., O. confundibilis n. sp., O. dabicola n. sp., O. shalulimontis n. sp., O. bacillum n. sp., O. bimicrospinosa n. sp., O. sinotibetana n. sp., O. erlangmontis n. sp., O. sinoangulata n. sp., O. muyupingensis n. sp., O. taipingensis n. sp., O. microgranulifera n. sp., O. shimianensis n. sp., O. nanwutaiensis n. sp., O. erlangensis n. sp., O. dabamontis n. sp., O. liao n. sp., O. rhododendricola n. sp., O. daxuana n. sp., O. xichangensis n. sp., O. latesentiens n. sp., O. sinoexilis n. sp., O. antegranulosa n. sp., O. victrix n. sp., O. tronqueti n. sp., O. taibaimontis n. sp., O. microlutea n. sp. Every new species is illustrated and compared with the aedeagus and the spermatheca of similar species. Distributional data are reported for 11 species.SommarioDescrizione di 47 nuove specie del genere Oxypoda: O. yunnanicola n. sp., O. mediogranulosa n. sp., O. irrepta n. sp., O. sinopusilla n. sp., O. meandrifera n. sp., O. guanxianensis n. sp., O. mimobisinuata n. sp., O. implorans n. sp., O. hastata n. sp., O. hailuogouensis n. sp., O. tibetana n. sp., O. sinofortis n. sp., O. qionglaimontis n. sp., O. daxuemontis n. sp., O. dilatatiapex n. sp., O. tridentis n. sp., O. jiudingensis n. sp., O. cavazzutii n. sp., O. zhagaensis n. sp., O. sinoperexilis n. sp., O. confundibilis n. sp., O. dabicola n. sp., O. shalulimontis n. sp., O. bacillum n. sp., O. bimicrospinosa n. sp., O. sinotibetana n. sp., O. erlangmontis n. sp., O. sinoangulata n. sp., O. muyupingensis n. sp., O. taipingensis n. sp., O. microgranulifera n. sp., O. shimianensis n. sp., O. nanwutaiensis n. sp., O. erlangensis n. sp., O. dabamontis n. sp., O. liao n. sp., O. rhododendricola n. sp., O. daxuana n. sp., O. xichangensis n. sp., O. latesentiens n. sp., O. sinoexilis n. sp., O. antegranulosa n. sp., O. victrix n. sp., O. tronqueti n. sp., O. taibaimontis n. sp., O. microlutea n. sp. Ogni nuova specie è illustrata e comparata con l’edeago e la spermateca di specie simili. Sono riferiti dati aggiuntivi sulla distribuzione per 11 specie.KeywordsColeoptera, Staphylinidae, Aleocharinae, taxonomy, China.Nomenclatural Actsantegranulosa Pace, 2012 (Oxypoda (Bessopora)), spec. nov.daxuana Pace, 2012 (Oxypoda (Bessopora)), spec. nov.latesentiens Pace, 2012 (Oxypoda (Bessopora)), spec. nov.microlutea Pace, 2012 (Oxypoda (Bessopora)), spec. nov.sinoexilis Pace, 2012 (Oxypoda (Bessopora)), spec. nov.taibaimontis Pace, 2012 (Oxypoda (Bessopora)), spec. nov.tronqueti Pace, 2012 (Oxypoda (Bessopora)), spec. nov.victrix Pace, 2012 (Oxypoda (Bessopora)), spec. nov.xichangensis Pace, 2012 (Oxypoda (Bessopora)), spec. nov.irrepta Pace, 2012 (Oxypoda (Oxypoda)), spec. nov.mediogranulosa Pace, 2012 (Oxypoda (Oxypoda)), spec. nov.sinopusilla Pace, 2012 (Oxypoda (Oxypoda)), spec. nov.yunnanicola Pace, 2012 (Oxypoda (Oxypoda)), spec. nov.bacillum Pace, 2012 (Oxypoda (Podoxya)), spec. nov.bimicrospinosa Pace, 2012 (Oxypoda (Podoxya)), spec. nov.cavazzutii Pace, 2012 (Oxypoda (Podoxya)), spec. nov.confundibilis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.dabicola Pace, 2012 (Oxypoda (Podoxya)), spec. nov.daxuemontis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.dilatatiapex Pace, 2012 (Oxypoda (Podoxya)), spec. nov.guanxianensis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.hailuogouensis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.hastata Pace, 2012 (Oxypoda (Podoxya)), spec. nov.implorans Pace, 2012 (Oxypoda (Podoxya)), spec. nov.jiudingensis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.meandrifera Pace, 2012 (Oxypoda (Podoxya)), spec. nov.mimobisinuata Pace, 2012 (Oxypoda (Podoxya)), spec. nov.qionglaimontis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.shalulimontis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.sinofortis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.sinoperexilis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.sinotibetana Pace, 2012 (Oxypoda (Podoxya)), spec. nov.tibetana Pace, 2012 (Oxypoda (Podoxya)), spec. nov.tridentis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.zhagaensis Pace, 2012 (Oxypoda (Podoxya)), spec. nov.dahamontis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.erlangensis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.erlangmontis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.liao Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.microgranulifera Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.muyupingensis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.nanwutaiensis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.rhododendricola Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.shimianensis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.sinoangulata Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.taipingensis Pace, 2012 (Oxypoda (Sphenoma)), spec. nov.